70.2k views
0 votes
Given: F(x) = 2x - 4; GX) = 3x + 2; Hpx)=x2
Find FG H(2)
0 121
27
071

User Chirag B
by
4.4k points

2 Answers

1 vote
Answer

24

Explanation

The format of the question is convoluted, I will assume you mean:

F(x) = 2x - 4
G(x) = 3x + 2
H(x) = x^2

And you want to find FGH(2) ?

1) To evaluate H(2), substitute
x = 2 into the function H(x) = x^2

H(2) = 2^2 = 4

2) To evaluate G(H(2)) substitute
x = 4 (since this is value obtained from H(2)) into the function
G(x) = 3x + 2

G(4) = 12 + 2 = 14

3) To evaluate F(G(4)) substitute x = 14 into the function F(x) = 2x - 4

F(14) = 28 - 4 = 24

User Beatrice Lin
by
4.4k points
4 votes

Answer:

FG H(2) = F*G*H(2) = 0

Explanation:

Your F(x) = 2x - 4; GX) = 3x + 2; Hpx)=x2 requires a bit of guesswork for the reader to understand it. I believe you meant:

F(x) = 2x - 4; G(X) = 3x + 2; H(x)=x2 Find FG H(2)

First find F(2): f(2) = 2(2) - 4 = 0

Because this multiplicand is zero, further multiplication will result in zero also. Thus, the final answer is zero (0).

User Robert Kossendey
by
5.2k points